Effect of Dietary Supplementation of Probiotic Bacteria Obtained from Fermented Tchoukoutou on the Production Performance of Local and Exotic Guinea Fowl - Glago, J.; Tchekessi, C.K.C.; Ekpo, K.J. (ANSINET, 2021)
Background and Objective: The use of antibiotic in livestock production has led to the emergence of new strains of pathogenic bacteria resistant to antibiotics. This study aimed to evaluate the effect of feed containing Lactobacillus casei, Lactobacillus fermentum, Lactobacillus acidophilus and Enterococcus faecium obtained from fermented Tchoukoutou on the performances of local guinea fowl and the exotic guinea fowl (Numida meleagris). Materials and Methods: The birds were assigned to 3 experimental treatments, namely R1 group received a diet containing 3% fermented Tchoukoutou, R2 group fed basal diets and R3 group fed basal diet with an antibiotic (Alfaceryl). A total of 375 guinea-fowl of the local strain and the exotic strain was allotted to each group at the pre-experimental phase were allotted to each group which lasted for one week. Results: The results showed that supplementation of probiotic bacteria improved the production performance of local guinea fowl especially at the starter phase whereas the production performance of the exotic birds were not affected. Conclusion: It was concluded that the feed containing probiotic bacteria obtained from the fermented Tchoukoutou had a beneficial effect on the growth performance of local guinea fowl.
Int.J.Poult.Sci.,20(5):224-230,2021
Keywords: Probiotic; Antibiotics; Guinea fowl; Growth performance; livestock production; C.C. Kpomassè; N.W. Chabi; A.K. Tete-Benissan; F.M. Houndonougbo; K. Tona; C.A.A.M. Chrysostome; Université de Lomé; CERSA